The relation between refugees' arrival in 2015-2016 and skills recognition at the European level and in Germany - Windisch, Hendrickje Catriona [Verfasser] (My University, 2020)
"The influx of asylum seekers into the European Union in 2015-2016 has turned the recognition of non-formal and informal learning (NFIL) into an integration priority. As refugees should be able to build on their existing skills and knowledge, such skills recognition is thought to facilitate their labour market integration. Therefore, for Germany and many other host countries, improving the accessibility and suitability of such mechanisms to refugees has become an integration challenge. This article explores why many European countries including Germany have been slow to address the issue systematically. It sheds light on the historical emergence of skills recognition at the EU level and the current implementation of skills recognition across European countries before zooming in on the situation of validation in Germany." (author's abstract; BIBB-Doku)
Keywords: P 1.5 Migranten; L 2.1.1 Informelles Lernen; Flüchtling; Informelles Lernen; Non-formales Lernen; Informelle Kompetenz; Anerkennung; Europäische Union; Bundesrepublik Deutschland